2015
DOI: 10.3390/molecules200713374
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Antihyperglycemic Activity of a Lanosteryl Triterpene from Protorhus longifolia

Abstract: Control of postprandial hyperglycemia is crucial in the management of diabetes mellitus. Despite the use of the current hypoglycemic drugs, incidence of diabetes and related diseases continue to increase. This study aimed at evaluating the in vivo antihyperglycemic activity of methyl-3β-hydroxylanosta-9,24-dien-21-oate (RA-3), a lanosteryl triterpene isolated, and characterized from Protorhus longifolia stem bark. Spectroscopic data analysis was used to establish and verify the structure of the triterpene. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…Some reported bioactivities of RA-3, which include anticoagulant, anti-inflammatory (Mosa 2014), antihyperglycemic (Mosa et al 2015) and antihyperlipidemic (Machaba et al 2014) activities, are all indicative of the potential cardioprotective effect of the triterpene. The results obtained from this study confirmed that the lanosteryl triterpene [methyl-3b-hydroxylanosta-9, 24-dien-21-oate, RA-3] possesses the cardioprotective effect.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Some reported bioactivities of RA-3, which include anticoagulant, anti-inflammatory (Mosa 2014), antihyperglycemic (Mosa et al 2015) and antihyperlipidemic (Machaba et al 2014) activities, are all indicative of the potential cardioprotective effect of the triterpene. The results obtained from this study confirmed that the lanosteryl triterpene [methyl-3b-hydroxylanosta-9, 24-dien-21-oate, RA-3] possesses the cardioprotective effect.…”
Section: Resultsmentioning
confidence: 99%
“…The observed increased serum GSH content and CAT activity, along with a decrease in MDA content (Table 2) in the triterpene pretreated group is indicative of the compound's ability to exert its cardioprotective effect through increasing the tissue antioxidant capacity. The ability of RA-3 to increase endogenous antioxidant capacity has also been demonstrated in streptozotocin (STZ)-induced diabetic animals (Mosa et al 2015).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…9 Flavonoid, triterpen and alkaloids are known for their antihyperglycemic effect. [10][11][12][13] Flavonoid impedes glucose absorption by blocking the GLUT-2 transporter in the small intestine. 14 From these active substrate contained inside, it is highly expected that Ageratum conyzoides…”
Section: Introductionmentioning
confidence: 99%